Microleakage of Single-Cone Gutta-Percha Obturation Technique in Combination with Different Types of Sealers - Sadr, Saeedeh (Iran Endod J, 2015)
INTRODUCTION: Various materials and methods have been recommended for successful root canal obturation. The aim of this experimental in vitro study was to compare the sealing ability of three root canal sealers AH-26, glass ionomer cement (GIC) and zinc oxide eugenol (ZOE) in single gutta-percha obturating system. METHODS AND MATERIALS: Seventy extracted single-rooted human teeth were decoronated. The teeth were randomly divided into 3 experimental groups (n=20) and 2 positive and negative control groups. After root canal preparation, canals were obturated with single-cone method using either AH-26, GIC and ZOE. The leakage was evaluated using the dye penetration method. The samples were sectioned to evaluate the linear leakage using a stereomicroscope. The data were analyzed using the One-way ANOVA test. RESULTS: All the specimens in the positive control group showed evidence of leakage. In the experimental groups, the lowest leakage scores were observed in the AH-26 group (P<0.05). However, there were no statistically significant differences between GIC and ZOE samples (P=0.676). CONCLUSION: AH-26 showed a superior seal and less microleakage compared to the two other materials in single gutta-percha obturating system.